Fichte, Eberhard, and the Psychology of Religion - Crowe, Ben (Harvard theological review, 2010)
In marked contrast to much of twentieth-century psychology and philosophy, prevailing accounts of affect, emotion, and sentiment in the eighteenth century took these phenomena to be rational and, to a certain extent, cognitive.1 Because of a combination of disciplinary diffusion and general lack of physicalist assumptions, accounts of affectivity in the eighteenth century also tended to be quite flexible and nuanced. This is particularly true of an influential stream of Anglo-Scottish and German thought on morality, aesthetics, and the philosophy of religion. Following Shaftesbury, many of the most prominent philosophers of the century regarded affective states and processes as playing a crucial role in accounts of value. In most cases, this tendency was combined with a sort of anti-rationalism, that is, with a tendency to minimize the role of reason in everything from common sense perceptual knowledge to religious belief. Hutcheson's moral sense theory and his well-known and influential criticisms of moral rationalism exemplify this trend.2 It is perhaps more pronounced in Lord Kames, who followed the lead of Shaftesbury and Hutcheson in aesthetics, moral theory, philosophy of religion, anthropology, and history.3 In Germany, this stream of thought was quite well-received by philosophers both inside and outside the dominant Wolffian tradition.4 Particularly important and influential in this respect were Johann Georg Hamann, who drew upon Hutcheson, Hume, and the “Common Sense” school to defend a conception of faith as “sentiment (Empfindung),” and Johann Gottfried Herder, a polymath and philosophical pioneer whose work in psychology, anthropology, history, aesthetics, biblical criticism, and theology consistently stresses the fundamental role of passion, affect, and sensibility in every aspect of human culture.5